Measuring macroeconomic uncertainty: A cross-country analysis - Andreas Dibiasi; Samad Sarferaz (ETH Zurich, KOF Swiss Economic Institute, 2020)
This paper constructs internationally consistent measures of macroeconomic uncertainty. Our econometric framework extracts uncertainty from revisions in data obtained from standardized national accounts. Applying our model to quarterly post-WWII real-time data, we estimate macroeconomic uncertainty for 39 countries. The cross-country dimension of our uncertainty data allows us to identify the effects of uncertainty shocks on economic activity under different employment protection legislation. Our empirical findings suggest that the effects of uncertainty shocks are stronger and more persistent in countries with low employment protection compared to countries with high employment protection. These empirical findings are in line with a theoretical model under varying firing cost.
hdl:20.500.11850/420180
Keywords: C51; C53; C82; E32; J8; 330; Uncertainty Shocks; Real-Time Data; Rational Forecast Error; Systemof National Accounts; Employment Protection Legislation